2018
DOI: 10.1177/1947603518770256
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glucose Levels Preserve Glucose Uptake, Hyaluronan Production, and Low Glutamate Release Following Interleukin-1β Stimulation of Differentiated Chondrocytes

Abstract: Objective Chondrocytes are responsible for remodeling and maintaining the structural and functional integrity of the cartilage extracellular matrix. Because of the absence of a vascular supply, chondrocytes survive in a relatively hypoxic environment and thus have limited regenerative capacity during conditions of cellular stress associated with inflammation and matrix degradation, such as osteoarthritis (OA). Glucose is essential to sustain chondrocyte metabolism and is a precursor for key matrix components. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…Restoration processes seem to have even better effects when cells are incubated in high-glucose conditions. High glucose has some anti-inflammatory effects [29,30]. In the present study, bupivacaine at extremely low concentrations in the presence of high glucose attenuated 5-HT-evoked intracellular Ca 2+ release in LPS-induced inflammatory astrocytes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Restoration processes seem to have even better effects when cells are incubated in high-glucose conditions. High glucose has some anti-inflammatory effects [29,30]. In the present study, bupivacaine at extremely low concentrations in the presence of high glucose attenuated 5-HT-evoked intracellular Ca 2+ release in LPS-induced inflammatory astrocytes.…”
Section: Discussionsupporting
confidence: 52%
“…However, this triple combination showed effects on glutamate-evoked Ca 2+ signaling only. Sildenafil has anti-inflammatory effects at very low concentrations [27,29,30,40], and by testing the substance at different concentrations, we found that sildenafil attenuated ATP-evoked intracellular Ca 2+ release at low concentrations [28]. The combination of sildenafil and the above drugs particularly affects glutamate- and ATP-evoked Ca 2+ signaling [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this astrocytic metabolism, which consumes ATP, Na + /K + -ATPase activity is increased. Increased lactate release as a result of increased glucose uptake and glucose flux through the glycolytic pathway might contribute to anti-inflammatory cellular actions by inhibiting glutamate release (35). Glucose transport in low-grade inflammation and in autoimmune diseases is changed.…”
Section: Low-grade Inflammation Can Lead To Systemic Inflammationmentioning
confidence: 99%
“…HMW-HAs are further processed and broken down to low-molecular-weight (LMW)-HAs (<120 kDa). These smaller HA fragments have been proposed to play roles in many chronic diseases including diabetes, autoimmune diseases, inflammation and cancer [7,8,9,10]. Strategies to reduce LMW-HA production or action have therefore been undertaken in animal models and pre-clinical studies, including adoption of the Food and Drug Administration (FDA)-approved drug 4-MU, an inhibitor of HA biosynthesis [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%